Semiotics and legal theory - "Jackson , Bernard S." (London, 1987)
Legal semiotics is a new discipline which has given rise to considerable interest among scholars especially in Britain, the United States, Continental Europe and South America. This book, newly available in paperback, presents the first systematic analysis of the relationship between contemporary semiotic theory and modern jurisprudence. Taking two very different intellectual traditions, structuralist semiotics as represented by A. J. Greimas and modern (mostly positivist) legal theory as represented by Hart, MacCormick, Dworkin and Kelsen, and juxtaposing them, Professor Jackson lays the foundation for a semiotic theory of law.
Keywords: Semantics (Law)